Convergent lines of evidence support LRP8 as a susceptibility gene for psychosis - Li, Ming; Rietschel, Marcella (Molecular neurobiology, 2016)
Reelin (RELN) is identified as a risk gene for major psychiatric disorders such as schizophrenia (SCZ) and bipolar disorder (BPD). However, the role of its downstream signaling molecule, the low-density lipoprotein receptor-related protein 8 (LRP8) in these illnesses is still unclear. To detect whether LRP8 is a susceptibility gene for SCZ and BPD, we analyzed the associations of single nucleotide polymorphisms (SNPs) in LRP8 in a total of 47,187 subjects (including 9379 SCZ patients; 6990 BPD patients; and 12,556 controls in a screening sample, and 1397 SCZ families, 3947 BPD patients, and 8387 controls in independent replications), and identified a non-synonymous SNP rs5174 in LRP8 significantly associated with SCZ and BPD as well as the combined psychosis phenotype (P meta = 1.99 × 10−5, odds ratio (OR) = 1.066, 95 % confidence interval (CI) = 1.035-1.098). The risk SNP rs5174 was also associated with LRP8 messenger RNA (mRNA) expression in multiple brain tissues across independent samples (lowest P = 0.00005). Further exploratory analysis revealed that LRP8 was preferentially expressed in fetal brain tissues. Protein-protein interaction (PPI) analysis demonstrated that LRP8 significantly participated in a highly interconnected PPI network build by top risk genes for SCZ and BPD (P = 7.0 × 10−4). Collectively, we confirmed that LRP8 is a risk gene for psychosis, and our results provide useful information toward a better understanding of genetic mechanism involving LRP8 underlying risk of complex psychiatric disorders.
Gesehen am 27.03.2019
Published online: 4 December 2015